Carbon nanotube-zeolite composite catalyst - characterization and application. Issue 5 (25th March 2021) - Prekob, Ádám; Hajdu, Viktória; Fiser, Béla; Kristály, Ferenc; Viskolcz, Béla; Vanyorek, László
Abstract: "Support on support" (SoS) core-shell nanostructure was prepared by using zeolite beads as supports for nitrogen-doped bamboo-like carbon nanotubes (N-BCNTs). The N-BCNTs were synthetized with catalytic chemical vapor deposition (CCVD) onto the surface of the beads to use later as primary catalyst support. On the SoS composite Pd, Rh, and Pt nanoparticles were successfully deposited (2 w/w%) with high dispersity. The prepared three catalytic systems (Pd-, Rh- and Pt-SoS) were characterized and tested in butene hydrogenation. The reactions were followed by FTIR spectroscopy. The butene conversion reached the maximum after about 6 minutes. Each catalyst was easy to handle and applicable in the studied reaction. Graphical Abstract: